2007
DOI: 10.1002/cbic.200700183
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of a Fully Functional Cyclotide inside Living Bacterial Cells

Abstract: Perfect circle. We report the biosynthesis of a natively folded cyclotide, MCoTI‐II, in E. coli by intracellular backbone cyclization of a linear cyclotide–intein fusion precursor. The cyclized peptide then spontaneously folds into its native conformation. Biosynthetic access to correctly folded cyclotides allows the possibility of generating cell‐based combinatorial libraries that can be screened, inside living cells, for their ability to modulate or inhibit cellular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(171 citation statements)
references
References 34 publications
(41 reference statements)
5
162
0
4
Order By: Relevance
“…56 In the work presented here, the first cyclotide 20 inhibitors of the foot-and-mouth viral 3C protease are reported, 48,57 based on a re-engineered MCoTI-II cyclotide scaffold. Though the potency of these first generation inhibitors is moderate (low μM), it is notable that cyclotides based on a trypsin inhibitor scaffold exhibit activity against 25 this cysteine protease. We anticipate that the efficient chemical and chemoenzymatic routes presented here will be readily adapted to ligation, screening and in situ purification of cyclotidebased libraries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…56 In the work presented here, the first cyclotide 20 inhibitors of the foot-and-mouth viral 3C protease are reported, 48,57 based on a re-engineered MCoTI-II cyclotide scaffold. Though the potency of these first generation inhibitors is moderate (low μM), it is notable that cyclotides based on a trypsin inhibitor scaffold exhibit activity against 25 this cysteine protease. We anticipate that the efficient chemical and chemoenzymatic routes presented here will be readily adapted to ligation, screening and in situ purification of cyclotidebased libraries.…”
Section: Discussionmentioning
confidence: 99%
“…Boc-, 38 microwave-enhanced 24 and Fmoc- 14,30,34,35 based solid-phase peptide synthesis (SPPS) have all been used for cyclotide backbone construction, whilst recent work has shown that bacterial expression can also be an effective approach for 20 smaller scale production of the cyclotide backbone. 25,28 Backbone cyclisation may then be achieved by exposing a suitably side chain protected backbone peptide bearing an amino N-terminus and a carboxy C-terminus to standard peptide coupling conditions, but this approach suffers from 25 multiple drawbacks including poor peptide solubility and the need for high dilution. Thia-zip native chemical ligation (TZ-NCL), a technique first pioneered by the Tam group, 39,40 has emerged as the most effective method for backbone cyclisation of cysteine-rich cyclic peptides, and is particularly 30 applicable to the synthesis of cyclotides.…”
Section: Chemical Synthesis Of Engineered Mcoti Cyclotidesmentioning
confidence: 99%
See 3 more Smart Citations